EMPIRICAL INDICATORS OF TEACHERS’ PROFESSIONAL SELF-FULFILLMENT - Gredinarova, Yana (PSYCHOLOGICAL JOURNAL, 2020)
The article determines the empirical indicators of teachers’ professional fulfilment, analyses characteristics and peculiarities of professional activities related to professional fulfilment. The study sample included 306 teachers of secondary schools, gymnasiums and lyceums. The research method was the questionnaire determining professional self-actualization, which contained 5 scales in an adapted version: professional self- fulfilment; satisfaction with professional development and activities; attitude to innovation, a new, creative approach to work; professional autonomy; organizational (educational institution) resources for self-realization. The study results has showed that, on the whole, teachers’ professional self-fulfilment, their satisfaction with professional development and professional work, attitudes towards innovation in their work and professional autonomy are at approximately the same level - above average. The least resourceful were the opportunities and conditions for professional self-fulfilment. As for teacher’s professional self-fulfilment, it is most important for them to achieve high results in their work and be aware of their professional goals and objectives. Such characteristics as autonomy in professional work, their attitude to innovations, professional satisfaction, and resources of their educational institution also were significant and influenced professional self-fulfilment. Teachers’ autonomy in their professional work was fairly high, it was ensured mainly by the independent solution of work tasks and sufficient amount of free time. Attitudes towards innovations and creative approach to work were fairly high also, especially for such indicators as interest in new approaches and their use in work, as well as the need for new knowledge, which contributed to the continuous expansion of ideas about the profession thanks to new knowledge. Teachers’ satisfaction with their professional work was also above average and supported, first of all, by their beliefs in the importance of the teacher’s profession. The assessment of the educational institution resources (capabilities) for self-fulfilment was rated the lowest among all studied indicators, however, it was still above the average. All the indicators have significant correlations: innovation, job satisfaction, professional autonomy, educational institution resources – these are conditions for a teacher’s professional growth, which together support professional self-fulfilment and the achievement of high professionalism.